Criminalization of Commercial Sex Service Users: A Comparative Study of Prostitution Eradication in Sweden and South Korea - Rizky Chandra Pratama (Media Hukum Indonesia (MHI), 2026)
Article 12 of Law No. 12 on Sexual Violence Crimes explicitly recognizes sex workers as victims of sexual exploitation. Nevertheless, it is primarily pimps who are subject to criminalization, while clients of commercial sex services remain free from legal consequences. This study aims to analyze whether commercial sex service users can be prosecuted and how criminal law regulations regarding commercial sex service users in Indonesia compare with those in Sweden and South Korea. The research method employed is a normative legal study utilizing a statutory approach, a conceptual approach, and a comparative approach. The findings indicate that users of commercial sex services cannot be prosecuted because there is no provision in the Criminal Code (KUHP) or any special legislation prohibiting the act of purchasing or using another person’s sexual services. Indonesia’s criminal law framework lags far behind that of Sweden and South Korea, which have criminalized the purchase of sex; in Indonesia, however, sex buyers or clients remain entirely beyond the reach of the law, even though sex buyers and pimps are interdependent within the ecosystem of prostitution and sexual exploitation.